Antimicrobial stewardship programme implementation in the UAE: perspectives of key stakeholders using Consolidated Framework for Implementation Research - N., Hashad (2023)
BackgroundMany studies report antimicrobial stewardship programme (ASP) implementation, but these are limited by a lack of theoretical underpinning. This may lead to missing key factors that are likely to influence the successful or unsuccessful implementation. AimTo explore key stakeholders' perspectives of ASP implementation in UAE hospitals, with a focus on facilitators and barriers. MethodsThe study employed a qualitative approach using semi-structured interviews conducted with ASP stakeholders involved in clinical use of antimicrobials at the individual patient level and including ASP team members and non-members. An interview schedule based on published literature and grounded in the Consolidated Framework for Implementation Research (CFIR) was developed, reviewed, and piloted. Recruitment was via purposive and snowball sampling. Interviews were recorded, transcribed, and thematically analysed by two independent researchers using CFIR as a coding framework. FindingsData saturation was achieved at 31 interviews. Multiple CFIR constructs were identified as implementation facilitators or barriers. Facilitators included external policy requirements (both national and international), leadership support, stakeholders' engagement, collaborative culture, effective communication, and forward planning. Barriers included blame culture, complexity of ASP implementation, and a shortage of expert personnel. ConclusionNumerous facilitators and barriers to ASP implementation from a stakeholders' perspective were identified in this research. The value of early leadership engagement to support provision of required resources, a need for effective planning and establishment of multiple engagement techniques, and valuable communication with healthcare providers are the main recommendations emerging to support improvement in clinical practice.